Effect of seed age on germination, and seedling survival of Lophophora diffusa (Cactaceae) - Briseño-Sánchez, Ma. Isabel; Nava-Osorio, Jade; Rojas-Aréchiga, Mariana; Mandujano, María C. (Instituto de Ecología, A.C., 2024)
Background and Aims: The ability to form a seed bank is one of the strategies that allow the population regeneration of species in unpredictable environments. Positive photoblastism, ecological longevity, seed size and dormancy mechanisms are usually attributes of seeds that are able to form a seed bank. In this study, we evaluated the effect of seed age on germination and survival of Lophophora diffusa, a cactus endemic of the Queretaro-Hidalgo semidesertic region, with the objective to identify their potential to form a seed bank. Methods: An experimental design was developed taking seed age as a factor, with seeds collected in the year the experiment was conducted (2018), and four-year-old seeds (collected in 2014). Germination and seedling survival were recorded at 15 observation times every third day. Germination results were analyzed using an "event-time" model with a log-logistic function fit, and a t-test was performed to determine differences between the estimated parameters. Survival results were analyzed using a generalized linear model with binomial error distribution and logit-link function. Key results: Although older seeds had a higher mean germination time compared to recently dispersed seeds, seed age did not affect germination and seedling survival. Studied seeds remained viable under laboratory conditions up to four years, with germination and survival percentages >50% regardless of seed age. Conclusions: The ability of seeds to remain viable for up to four years under laboratory conditions, together with the morphological and physiological characteristics known for this species, indicate its potential to form a short-term persistent seed bank.